STUDY THE INDONESIAN LANGUAGE TEXTBOOK CLASS X INDEPENDENT CURRICULUM PUBLISHED BY YUDHISTIRA - Regita Amelia; Sabrina Pramesuary; Dwi Nanda; Yulisin Nazra; Inayah Hanum; Safinatul Hasanah Harahap (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This research aims to determine (1) the suitability of the content, (2) the suitability of the language, and (3) the suitability of presenting the Indonesian language textbook, namely "Cakap Bahasa dan Bersastra Indonesia" published by Yudhistira for class X SMA/MA/SMK students. The type of research used in this research is qualitative descriptive research. The research instruments used in this research are indicators from the observed aspects which include the appropriateness of the material, language and presentation of the textbook. The data collection technique used is the note-taking technique. The data analysis techniques used consist of identifying, classifying, interpreting and concluding. The results of this research prove that the textbook “Cakap Berbahasa dan Bersastra Indonesia” published by Yudhistira for class the current independent curriculum, especially for class X students.